The Evolution of Time: Studies of Time in Science, Anthropology, Theology - Nicolaidis, Argyris; Achtner, Wolfgang (Bentham Science Publishers, 2013)
Time - a fundamental component of human thought and experience - is quite enigmatic and elusive when it comes to defining it. In this e-book, scholars from the fields of physics, mathematics, biology, neuroscience, psychology, philosophy and theology draw from their own field of knowledge and expertise and present their understanding of the time phenomenon